Electronic Linguodidactic Tools for the Study of Classical Languages by Foreign Medical Students at a Russian Regional University - Flera Ya. KHABIBULLINA; Iraida G. IVANOVA; Nikolaj A. KIRILLOV; Nadezhda V. SMIRNOVA (Communications of International Proceedings, 2021)
The purpose of this article is to analyze electronic educational online resources for learning the Latin language on the Internet, recommended for foreign students studying at Russian universities. The materials act as linguodidactic means of teaching phonetics, grammar, vocabulary, regional studies and meet the following requirements: authenticity; lexical and semantic variability; professionally oriented character; consistency; availability and openness; versatility; multilingualism; linguocultural potential. A review of medical websites in online and offline environments was carried out. Linguistic training systems are subdivided into online courses for teaching the Latin language, training exercises and control tests, terminological reference dictionaries.
Keywords: Electronic Resource; Online Course; Electronic Educational Course; Latin Language; Foreign Students.